Factor Analysis on the Quality of Licensing Services via Online Single Submission (OSS) for Smes in Semarang Central Java Province - Ismowati, Mary; Sujono, Sujono; Atmanegara, Intan (Jurnal Manajemen Pelayanan Publik, 2024)
This research discusses the quality factors of SME licensing services carried out by the Semarang City Cooperatives and Micro Enterprises Service. Researchers are interested in raising this topic because the program being held is an effort to provide convenience in licensing for SME business development, but deficiencies were found in the smoothness of the OSS application process. This research is descriptive quantitative using primary and secondary data sources. The sample was obtained using random sampling techniques. Observations and questionnaires were used to conduct collection techniques. The analysis technique uses Kaiser Meyer Olkin (KMO). There are 30 question attributes grouped into 5 dimensions. The results of the research formed 6 new factors, where the most dominant factor in the quality of OSS licensing services for SMEs amounting to 45.4% was the quality of the OSS licensing application, easy to use, flexible, convenience and speed of online licensing services. Meanwhile, the factor with the smallest value of 5.14% is the timeliness of permits. It is hoped that permits can be issued on time according to time standards.